The impact of the digital revolution on the global economy - Imamov, Marsel; Semenikhina, Natalia (Linguistics and Culture Review, 2021)
Today, the economy is undergoing serious changes based on new digital technologies and artificial intelligence, which has affected serious qualitative and structural shifts. The purpose of this work is to study the impact of new technologies on economic processes, the advantages and disadvantages of the rapid development of new technologies. The significance of the research is determined by the relevance of the topic of the work, as well as the importance of tracking the processes of the world economy. The authors conducted a study and revealed that the digital economy is influenced by trends in the use of modern technologies, described the consequences of these changes, as well as the possibility of preventing problems. Globalization, integration, acceleration of integration processes, industrialization, environmental, demographic and political factors of economic life around the world require balanced development of the national economy with special attention. This article examines the ways of economic development and the following consequences. Analysing the results, it can be noted that it is impossible to say unequivocally what can negatively or positively affect the development of the digital economy, because there is an unpredictability factor that needs to be constantly taken into account in research.